SUMBER BELAJAR EKOLOGI: FEKUNDITAS IRAN SERIBU (Lebistes reticulatus Peters.) DIPERAIRAN SUNGAI GAJAH WONG, YOGYAKARTA (TEACHING MATERIALS ON ECOLOGY: FECUNDITY OF "SERIBU" FISH (.Lebistes reticulatus Peters) ON POLLUTED AND NON POLLUTED AREA OF GAJAH WONG RIVER, YOGYAKARTA) - Arief Abdillah Nurusman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2006)
This research was aimed to know the influence of water quality and pollution on fecundity of Lebistes reticulatus Peters. The result of this research will show how environmental factors act toward the organism on several levels of ecological hierarchy. The disscussion of it then will enrich student's understanding about the effect of environmental fastors toward the organism. That is the material to learn. This research was carried out upon Gajah Wong river precisely on water mass which polluted by tannery waste and the water mass out of polluted area. Three sampling were carried out along the trasect which cover the befor- polluted area, the outlet of waste and the water mass polluted by the waste. Embrio was then counted for measure the fecundity. The result shows that pollution affect the fecundity of Lebistes reticulatus by turning the fecundity lower. Pollution caused the change of dissolved oxygen and water acidity from its normal condition. Indeed, pollution caused the low environmental quality, even for reproduction of the more-tolerannt fish. Disscussion upon that result will enrich student's understanding about the effect of pollution toward living thing. By carrying the student into the field during teaching and learning proccesses and practicing on ecology, the understanding will go into effectively.